2010
DOI: 10.1007/s00392-010-0185-z
|View full text |Cite
|
Sign up to set email alerts
|

One-year clinical outcomes with abciximab in acute myocardial infarction: results of the BRAVE-3 randomized trial

Abstract: In patients with STEMI, all receiving 600 mg clopidogrel, abciximab did not improve overall clinical outcomes at 1 year after primary coronary stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The BRAVE‐3 trial which randomized patients to abciximab or placebo did not show any clinical benefit at 30 days. But significant reduction in infarct related artery revascularization was seen at one year .…”
Section: Discussionmentioning
confidence: 91%
“…The BRAVE‐3 trial which randomized patients to abciximab or placebo did not show any clinical benefit at 30 days. But significant reduction in infarct related artery revascularization was seen at one year .…”
Section: Discussionmentioning
confidence: 91%
“…In the ON-TIME 2 Trial, the patients who received high-dose bolus Tirofiban (25 mcg/kg) before primary PCI exhibited a strong trend toward a decrease in mortality (2.2 % vs. 4.1 %, P = 0.051), which was maintained during one year's follow-up (3.7 % vs. 5.8 %, p value = 0.08) (30). In contrast, Abciximab-facilitated PCI in FINESSE Trial improved neither a composite of death from all causes, ventricular fibrillation occurring more than forty-eight hours after randomization, cardiogenic shock, and congestive heart failure during the first ninety days after randomization (31) nor one year's mortality (32). BRAVE 3 Trial reported no effect for the early administration of Abciximab on a composite of death, recurrent myocardial infarction, stroke, or revascularization of the infarct-related artery at thirty days (22) and one year's follow-up (33).…”
Section: Discussionmentioning
confidence: 97%
“…No effect of early abciximab was found on clinical endpoints Harzard ratios (HR) and corresponding 95% Confidence intervals (CI) for the three individual endpoints mortality, target vessel revascularization (TVR), and myocardial infarction (MI), and the combination of those. [28]. In summary, trials evaluating early versus late administration of abciximab have detected some effect on clinical endpoint, but only in patients with the highest risk scores.…”
Section: Discussionmentioning
confidence: 98%